A Comparison of Energy Profile between Castilla Leon, Spain and Aceh, Indonesia - Mahidin, Mahidin; Khairil, Khairil; Martin, Carmen; Villamanan, Miguel A.; Segovia, Jose J.; Chamorro, Cesar R. (Jurnal Rekayasa Kimia & Lingkungan, 2010)
A comparative study on energy production and consumption between Aceh, Indonesia and Castilla Len, Spain has been conducted. Analysis was carried out on the statistical data such as population, GDP, energy production and energy consumption. Some interesting results were obtained. An average energy production during 2001 2004 in Aceh is up to 28 times of the average energy production in Castilla Len; however, the average energy consumption during those four years is only 16.74% of the average energy consumption of Castilla Len. Aceh's average GDP from 2001 to 2004 is 3,357.16 million Euros, stands at only 8.15% of Castilla Len's average GDP about 41,175.75 million Euros.Keywords: economic growth, final energy consumption, GDP, primary energy production